2015
DOI: 10.1038/srep14914
|View full text |Cite
|
Sign up to set email alerts
|

Polarization: A Key Difference between Man-made and Natural Electromagnetic Fields, in regard to Biological Activity

Abstract: In the present study we analyze the role of polarization in the biological activity of Electromagnetic Fields (EMFs)/Electromagnetic Radiation (EMR). All types of man-made EMFs/EMR - in contrast to natural EMFs/EMR - are polarized. Polarized EMFs/EMR can have increased biological activity, due to: 1) Ability to produce constructive interference effects and amplify their intensities at many locations. 2) Ability to force all charged/polar molecules and especially free ions within and around all living cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 35 publications
2
60
0
2
Order By: Relevance
“…Given that the incidence of cancer in male rats was barely statistically significant, a factor of 9 would predict no cancer observed in male mice. This observation of no cancer in male mice strongly argues against any cancer mechanism that is at the cellular or molecular level, like those suggested by Barnes and Greenebaum (2016) and Panagopoulos, Johansson, and Carlo (2015). Given that nerve cells are about the same size in mice and rats and the genetics and biology of mice and rats are extremely similar, a cellular or molecular theory of cancer would predict cancer in male mice, if there is cancer in male rats.…”
Section: Comparison Between Model and Experimentsmentioning
confidence: 94%
See 1 more Smart Citation
“…Given that the incidence of cancer in male rats was barely statistically significant, a factor of 9 would predict no cancer observed in male mice. This observation of no cancer in male mice strongly argues against any cancer mechanism that is at the cellular or molecular level, like those suggested by Barnes and Greenebaum (2016) and Panagopoulos, Johansson, and Carlo (2015). Given that nerve cells are about the same size in mice and rats and the genetics and biology of mice and rats are extremely similar, a cellular or molecular theory of cancer would predict cancer in male mice, if there is cancer in male rats.…”
Section: Comparison Between Model and Experimentsmentioning
confidence: 94%
“…Recently, Barnes and Greenebaum (2016) proposed that weak static and high frequency magnetic fields could change the recombination rate of radical pairs, and thus, change the concentration of carcinogenic radicals like O 2 -in cells. Panagopoulos, Johansson, and Carlo (2015) suggested that high frequency electric fields exert electrostatic forces on the cell membrane, disrupting the functioning of the ion channels.…”
Section: Previous Workmentioning
confidence: 99%
“…1). The nature of electromagnetic toroidal excitations as developed in physics wss reviewed by Papasimakis et al, 2016, and their interactions with inorganic matter by Tsytovich et al, 2007, while potential role as information collectors and carriers in life systems have been discussed by us earlier (Meijer and Geesink, 2016). We consider the following aspects: -The torus has a topology, with its internal channel-like structure (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…-The torus is a favored geometric structure in physics and is applied for the description of elementary particles from the micro-to macroscale of the entire universe (Papasimakis et al, 2016;Williamson, 1997;Tozzi, 2015;Merali, 2008;Poplawski, 201;van Putten, 2002;Haramein and Rauscher, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such electron leakage may be achieved through interference with proton transmission through the transmembrane complexes of the inner mitochondrial membrane. This is caused by the ability of modulated EMR (such as that emitted from mobile phones) to augment the oscillation of ions, interfering with their transport through membrane proteins, thus potentially perturbing the strict membrane potentials (Panagopoulos et al 2000(Panagopoulos et al , 2002(Panagopoulos et al , 2015 enforced in the specific intermembrane compartments of the mitochondria, which otherwise stabilise proton flow ( Fig. 3; Perry et al 2011).…”
Section: Metabolic Pathways Activated By Rf-emrmentioning
confidence: 99%